EFFECTS OF 8-WEEK ELECTRICAL MUSCLE STIMULATION ON THE MUSCLE CONTRACTILE PROPERTIES IN ADOLESCENT GIRLS - Sara Pregelj; Boštjan Šimunič (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2018)
The study aimed to determine the effect of 8-week unilateral electrical muscle stimulation (EMS) training of leg muscles: vastus lateralis, vastus medialis and biceps femoris with the same number of muscle contractions in comparison to controls. Contractile properties were monitored by measuring the maximal voluntary isometric contraction (MVC) and the rate of force development in first 50 ms (RFD50) of knee extensors and flexors and tensiomyography of stimulated muscles. In addition, we also investigated the retained effect after 8 weeks without EMS training. Nineteen healthy young female athletes aged 15 to 18 years (average 16.4 ± .9 years) were randomly divided in a control group (CG; N=8) and experimental group (EG; N=11). CG performed maximal unilateral voluntary contractions while the EG performed also EMS training of the same leg by stimulating both vasti muscles and biceps femoris. There were no changes in CG after 8-weeks of maximal unilateral voluntary training; however, EG improved MVC in knee extensors (12.6%; P =.085) and RFD50 (142.1%; P =.049) where RFD50 retained increased also 8 weeks after EMS training (73%; P =.090). Tensiomyography revealed decreased amplitude (13.2%; P=.011) only in EG, representing higher muscle tone after 8-weeks of EMS in comparison to CG. Our findings indicate that EMS training has a positive effect on muscle contractile properties in young female athletes even after comparing to matched controls by the number of contractions. Keywords: EMS, muscle strength, tensiomiography, rate of force development